Musgos da Gruta de Mirassol, São Paulo - Yano, Olga; Santos, Solange Xavier dos [UNESP] (Sociedade Botânica do Brasil, 1993)
Na Gruta de Mirassol foram encontradas 27 espécies de musgos pertencentes a 23 gêneros de 19 famílias. Racopilum tomentosum (Hedw.) Brid., Helicophyllum torquatum (Hook.) Brid. e Hyophila involuta (Hook.) Jaeg. & Sauerb. são as espécies mais abundantes. Brachymenium acuminatum Harv., Cyclodictyon varians (Sull.) O. Kuntze, Entodontopsis leucostega (Brid.) Buck & Ireland, Fissidens mollis Mitt., F. weirii Mitt., Hyophila involuta (Hook.) Jaeg. & Sauerb. e Trichosteleum fluviale (Mitt.) Jaeg. estão sendo referidas pela primeira vez para o estado de São Paulo.

Twenty-seven species of moss are described from the Gruta de Mirassol, State of São Paulo, Brazil; these are distributed among 23 genera and 19 families. Racopilum tomentosum (Hedw.) Brid., Helicophyllum torquatum (Hook.) Brid., and Hyophila involuta (Hook.) Jaeg. & Sauerb. are the most common species. Brachymenium acuminatum Harv., Cyclodictyon varians (Sull.) O. Kuntze, Entodontopsis leucostega (Brid.) Buck & Ireland, Fissidens mollis Mitt., F. weirii Mitt., and Hyophila involuta (Hook.) Jaeg. & Sauerb. are cited for the firtst time from São Paulo State.
Mosses from the Gruta de Mirassol, São Paulo State
Keywords: musgos; Bryopsida; Gruta de Mirassol-SP; distribuição geográfica; mosses; Bryopsida; Gruta de Mirassol-SP; geographical distribution